2020
DOI: 10.1016/s2468-1253(20)30190-4
|View full text |Cite
|
Sign up to set email alerts
|

Management of patients with liver derangement during the COVID-19 pandemic: an Asia-Pacific position statement

Abstract: on behalf of the Asia-Pacific Working Group for Liver Derangement during the COVID-19 Pandemic The COVID-19 pandemic has spread rapidly worldwide. It is common to encounter patients with COVID-19 with abnormal liver function, either in the form of hepatitis, cholestasis, or both. The clinical implications of liver derangement might be variable in different clinical scenarios. With growing evidence of its clinical significance, it would be clinically helpful to provide practice recommendations for various commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
112
0
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(127 citation statements)
references
References 74 publications
(72 reference statements)
2
112
0
13
Order By: Relevance
“…Biomarkers of multisystem organ failure/damage COVID-19 can be associated with liver injury during disease progression and treatment, in patients with or without preexisting liver disease. Elevated values of aspartate aminotransferase (AST), alanine aminotransferase (ALT) and bilirubin, and low albumin and prealbumin concentrations have all been associated with poor outcome [36][37][38] In addition, some drugs used in the treatment of COVID-19 are associated with the development of elevated liver biomarkers [39][40][41]. For this reason, at a minimum, it is recommended to monitor ALT, bilirubin and albumin during treatment of patients with hepatotoxic medications, and in those with pre-existing liver disease.…”
Section: Cardiovascular Biomarkersmentioning
confidence: 99%
“…Biomarkers of multisystem organ failure/damage COVID-19 can be associated with liver injury during disease progression and treatment, in patients with or without preexisting liver disease. Elevated values of aspartate aminotransferase (AST), alanine aminotransferase (ALT) and bilirubin, and low albumin and prealbumin concentrations have all been associated with poor outcome [36][37][38] In addition, some drugs used in the treatment of COVID-19 are associated with the development of elevated liver biomarkers [39][40][41]. For this reason, at a minimum, it is recommended to monitor ALT, bilirubin and albumin during treatment of patients with hepatotoxic medications, and in those with pre-existing liver disease.…”
Section: Cardiovascular Biomarkersmentioning
confidence: 99%
“…Studies looking at LFT in COVID-19 patients have also found that the majority had mild LFT abnormalities that were self-limiting [15][16][17] . Thus, other factors such as associated metabolic co-morbidities may contribute to the increased risk of severe COVID-19 infection in NAFLD patients 18 . We found that more patients in the NAFLD group had hyperlipidaemia as compared to those in the non-NAFLD group.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale and finalized lists of prioritized procedures is beyond the discussion of this review. Differing recommendations with regard to screening colonoscopy in fecal immunochemical test (FIT) positive patients 12,13,38 and patients requiring variceal screening [39][40][41][42] are a testament that this decision process in real-world settings is complex, and that a certain degree of discretion should be allowed for endoscopists when making such decisions. Some experts opine that FIT during COVID-19 could be used as a triage tool to guide timing and help prioritize investigations due to limited capacity, but at the end of the day these triage tests cannot entirely replace confirmatory tests such as colonoscopy 43 .…”
Section: Postpone Endoscopy For Patients With Non-urgent Indicationsmentioning
confidence: 99%